An investigation of aerosol particle number and size generated during a drilling process with surface coated tools. (21st July 2008) - Handy, Rodney G.; Jackson, Mark J.; Rodriguez, Monica; Goodman, David; Robinson, Grant; Lafreniere, Michael
The generation of aerosols has the potential to negatively impact the health of those exposed, including those of biological origin generated in the breathing zone of medical and dental workers during surface manipulations. A system capable of characterising the size and concentration of airborne particles generated during a drilling process on animal bone with surface-coated tools was recently developed and tested under controlled laboratory conditions. The effectiveness of a laminar flow ventilation unit, with an installed Ultra Low Penetration Air (ULPA) filter and ionisation bar, was evaluated for performance and particulate removal efficiency. Particles, ranging from 0.02 micron to greater than 5 micron, were monitored with both a portable laser particle counter and a Condensation Particle Counter (CPC). Future efforts will be aimed at improving the particulate removal efficiency through modifications in filter configurations and other system variables. In addition, a performance predictive algorithm will be developed and applied under both field and controlled laboratory conditions.